The Role of Innocent Guilt in Post‐Conflict Work. (30th September 2013) - Christensen, Anne‐Marie Søndergaard
Abstract: The phenomenon of 'innocent guilt' regards cases where people feel guilty without being responsible for the wrongdoing or suffering at which the guilt is directed. The aim of this article is to develop a consistent account of innocent guilt and show how it may arise in the aftermath of conflicts. In order to do this, innocent guilt is contrasted with guilt and collective guilt, and the account is substantiated by drawing on the writings of Ludwig Wittgenstein and Emmanuel Levinas, who both consider the phenomenon of innocent guilt a necessary element in the fundamental structure of the ethical subject. These thinkers, furthermore, show a connection between guilt and possible victims of wrongdoing, rather than between guilt and personal acts of wrongdoing. Innocent guilt may thus appear in the aftermath of conflicts as an ethical and emotional response to the fact of finding oneself in a post‐conflict situation still marked by suffering. It thus reveals a fundamental need to contribute to the relieving of such suffering.